Brain functional network integrity sustains cognitive function despite atrophy in presymptomatic genetic frontotemporal dementia - Tsvetanov, Kamen A. (2020)
© 2020 The Authors. Alzheimer's & Dementia published by Wiley Periodicals, Inc. on behalf of Alzheimer's Association. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.